Evaluation of the growth factors VEGF-a and VEGF-B in the vitreous and serum of patients with macular and retinal vascular diseases. (4th March 2018) - Mesquita, Joana; Castro-de-Sousa, João Paulo; Vaz-Pereira, Sara; Neves, Arminda; Passarinha, Luís A.; Tomaz, Cândida T.
Abstract: VEGF-A and VEGF-B are proangiogenic and key regulating factors for blood vessel growth. This study aims to compare VEGF-A and VEGF-B levels in the serum and vitreous of patients with neovascular pathology versus non-neovascular pathology. Our findings showed vitreous VEGF-A and VEGF-B levels increased in patients with neovascular disease, with higher levels of VEGF-A compared to VEGF-B ( p ≤ .05). In the diabetic retinopathy (DR) group, higher vitreous VEGF-A or VEGF-B were found in proliferative diabetic retinopathy (PDR) than in non-PDR. The strong correlation between VEGF-A and VEGF-B demonstrates a simultaneous pathological increase of cytokines ( p < .001), suggesting besides VEGF-A, VEGF-B is another contributor to ocular pathologies involving angiogenesis. There was no correlation between vitreous and serum VEGF-A or VEGF-B; however, a correlation between vitreous (VEGF-A or VEGF-B) and macular volume ( p < .05) in DR patients was found. Targeting VEGF-A and VEGF-B in macular and retinal vascular diseases, involving neovascularization, may improve treatment outcomes.